P‐207: Late‐News Poster: Optimized Pixel Design to Improve Image Sticking in Full‐Screen LCDs with Ultra Narrow Border. Issue 1 (29th May 2019) - He, Yanlin; Chen, BaoLing; Ling, Ankai; Shen, Poping; Li, Junyi
Abstract : We have proposed an optimized pixel design based on Width ＞ Space(abbreviation SFT‐Pro) to improve image sticking( IS ), the scheme has been demonstrated by theory simulation and variable‐controlled practical experiment.